Comparisons of Standard Time and MOST for Mill and Skive Housing Operation (International Journal of Innovative Research in Computer Science & Technology, 2017)
The purpose of this study was to compare  time study and motion study for mill and skive housing  operation and to recommend the improvement  methodologies for the productivity of the operation. The  original time study and the MOST were used to  evaluate this operation. The results showed that MOST  resulted in 0.372 minutes and the time study resulted in  0.55minutes.
Keywords: MOST; Time Study; Motion Study; Cycle; Operation